MENGGUGAH KESADARAN MASYARAKAT DALAM PENGELOLAAN SAMPAH MELALUI PEMBUATAN BAK SAMPAH DAN PLANG HIMBAUAN DI KELURAHAN PANJI SARI, KECAMATAN PRAYA LOMBOK TENGAH - Fatmayanti, Fatmayanti; Husnawati, Nila; Alieni, Karimannisa; Aulia, Natasya Difa; Paramesty, Ristawidya; Bahtiar, Gian Agisna; Hudaeri, Huzrullah; Azima, M. Fauzan; Khoarizmi, M. Syatho; Ngudiyono, Ngudiyono (Jurnal Wicara, 2023)
Kuliah Kerja Nyata (KKN) is a form of community service activities carried out by universities. In KKN activities carried out in Panji Sari Village, Praya District, Central Lombok Regency, groups of students and lecturers of Mataram University carry out various activities with the main target of Village Community Empowerment. Panji Sari is one of the villages located in Praya District, Central Lombok Regency, West Nusa Tenggara Province with an area of 118.33 Ha. The large area in the village also has environmental problems. The lack of public awareness of waste owned by this region is very alarming, this is due to the absence of Waste Disposal Sites (TPS) and Signs of Appeal for orderly waste disposal. Therefore, to increase public awareness of the dangers of waste and as a step towards a clean environment and minimize community littering, the KKN-PMD team made bamboo garbage bins and environmental appeal signs. The method used in this activity is counseling and demonstration. The community paid attention to the material presented during the socialization and then continued with the demonstration of making and assisting in making garbage bins and appeal signs. From the evaluation results, it was found that the community felt helped by this activity and gained knowledge about the dangers of waste for the surrounding environment.